Implementasi Sistem Informasi Tata Kelola Pemerintahan Desa Dalam Meningkatkan Pelayanan Masyarakat Melalui Desain User Interface Di Desa Pertumbukan Kec.Wampu - Yusman, Yanti; Putra, Randi Rian; Intan Sinaga (Jurnal Mahajana Informasi, 2024)
This Research aims to evaluate the implementation of yhe village governance information system and its impact on improving community services in Growth Village, Wampu District. The main focus of this research is user interface design which is expereted to facilitatee acces and use of the system by the community and village officials. The research methodology used include field studies, distributed to village residents and village officials.